2006
DOI: 10.2135/cropsci2005.05-0091
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Two Russian Wheat Aphid Biotypes to Eight Wheat Cultivars at Two Temperatures

Abstract: Biotype 2 of the Russian wheat aphid, Diuraphis noxia (Mordvilko), is virulent to both sources of resistance presently available in commercial wheat, Triticum aestivum L. The performance of biotype 2 was compared with that of biotype 1 on eight wheat cultivars at two constant temperatures, and the plants were evaluated for overall damage and leaf rolling. Colonies of biotype 2 grew an average of 2.3 and 24.9 times faster in the first and second generation, respectively, than did their biotype 1 counterparts at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
15
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
(24 reference statements)
4
15
1
1
Order By: Relevance
“…The reduced performance of RWA1 observed on both resistant cultivars is consistent with previous work (Haley et al 2004, Jyoti et al 2006. The juvenile survival of RWA1 was reduced on both resistant cultivars at 24ЊC, although only on Halt at 20ЊC, with the same pattern evident for both singles and groups.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The reduced performance of RWA1 observed on both resistant cultivars is consistent with previous work (Haley et al 2004, Jyoti et al 2006. The juvenile survival of RWA1 was reduced on both resistant cultivars at 24ЊC, although only on Halt at 20ЊC, with the same pattern evident for both singles and groups.…”
Section: Discussionsupporting
confidence: 90%
“…Cultivars of wheat vary in their suitability as food for D. noxia (Ali et al 1985, Jyoti et al 2006 and various "biotypes" of D. noxia are recognized based on their ability to damage cultivars expressing particular genetic sources of resistance (Basky 2003, Haley et al 2004. For example, a series of commercial cultivars bred speciÞcally for resistance to D. noxia express a gene designated Dn4, and these cultivars have been widely planted in regions of the United States where D. noxia has persistently caused economic losses (Randolph et al 2003, CASS 2004, whereas other sources of resistance such as Dny have not been planted as widely.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Trego (pedigree KS87H325/Rio Blanco) is a white winter wheat cultivar released by Kansas State University in 1999 (Martin et al 2001). We used Trego as a control because it was very susceptible to damage by both biotypes of D. noxia at 20 and 24ЊC (Jyoti et al 2006). CI 2401 is a line that originated in Tajikistan in the former USSR that was Þrst identiÞed as resistant to biotype 1 D. noxia in evaluations of land races by Harvey and Martin (1990), but it has not yet been released in a commercial cultivar.…”
Section: Materials Andmentioning
confidence: 99%
“…During the 2003 Á2004 growth season, two new biotypes were reported for the state of Colorado, and these overcame Dn4 (Haley et al 2004) and Dny-based resistance (Jyoti et al 2006). When the virulence of RWA biotype 2 was compared to that of RWA biotype 1, it was found that biotype 2 was more virulent to all cultivars tested, and induced plant injury more rapidly than biotype 1, especially at higher temperatures (Jyoti et al 2006). At least four new biotypes later appeared in Texas and in other western central US states.…”
Section: Introductionmentioning
confidence: 99%